(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The word "morpheme" consists of two morphemes: "morph" and "eme." The first morpheme "morph" is a free morpheme, meaning it can stand alone as a word with its own meaning. In this case, "morph" refers to form or shape. The second morpheme "eme" is a bound morpheme, meaning it cannot stand alone and must be attached to another morpheme. Bound morphemes typically modify the meaning of the free morpheme they are attached to.There are two main types of morphemes: free morphemes and bound morphemes. Free morphemes can stand alone as words, while bound morphemes must be attached to another morpheme. Bound morphemes can be further categorized into two subtypes: derivational morphemes and inflectional morphemes. Understanding the structure and types of morphemes is essential for analyzing and understanding the formation and meaning of words in a language